Lifetime Syphilis Prevalence and Associated Risk Factors Among Female Prisoners in Brazil. Issue 2 (February 2020) - da Silva Santana, Rosane; Kerr, Ligia; Mota, Rosa Salani; Kendall, Carl; Rutherford, George; McFarland, Willi
Abstract : Background: In 2016, approximately 42, 000 women were incarcerated in Brazil. The objectives of this study were to measure the lifetime prevalence of syphilis and sociodemographic and behavior correlates of antibody positivity among female prisoners in Brazil. Methods: We conducted a cross-sectional survey of 1327 incarcerated women in 2014 to 2015 sampled through a multistage cluster design to represent the penitentiary system throughout Brazil. A rapid treponemal antibody test approved by the Ministry of Health (Rapid Test DPP Sífilis Bio-Manguinhos) was used to detect lifetime history of infection. Analyses were adjusted using weights based on the inverse of the product of the probabilities of the sampling units at each stage of the design. Variables significantly associated with syphilis infection at P < 0.05 in multivariate analyses were retained in the final model. Results: Prevalence of syphilis antibody among female prisoners in Brazil was 11.6% (95% confidence interval [CI], 9.8%–13.8%). Higher syphilis prevalence was associated with black/Afro-Brazilian or mixed race/ethnicity (adjusted odds ratio [AOR], 1.78; 95% CI, 1.10–2.87), homelessness (AOR, 4.58; 95% CI, 2.78–7.56), abortion (AOR, 1.56; 95% CI, 1.02–2.38), and sexual violence (AOR, 1.59; 95% CI, 1.01–2.49). Syphilis prevalence was lower among women who had received condoms in school (AOR, 0.28; 95% CI, 0.08–1.00) as a marker for reproductive health education. Conclusions: Women within the vast Brazilian prison system demonstrate a high lifetime cumulative incidence of syphilis. Our data advocate for increased screening and treatment of syphilis of incarcerated women and help identify women at higher risk within the prison system and within their communities of origin. Abstract : A survey of the female prison population of Brazil found a lifetime syphilis prevalence of 11.6%, with higher levels among black/Afro-Brazilians and women with a history of homelessness, abortion, and sexual violence.